1999
DOI: 10.1007/s004170050201
|View full text |Cite
|
Sign up to set email alerts
|

The contrast characteristic of the pattern electroretinogram depends on temporal frequency

Abstract: This dependency of the contrast characteristic on temporal frequency is contrary to what would be expected from a magno/parvo model. Further, this contrast dependency needs to be taken into account when designing stimuli for use in patients that may have media opacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 37 publications
1
8
0
3
Order By: Relevance
“…The effects are readily understood when the low-pass nature of defocus [92][93][94] and the PERGs linear contrast-amplitude characteristic are taken into account. 49,51 To avoid false positive results, we perform PERG-glaucoma testing only on eyes with a visual acuity Ն0.8, tested at the PERG-stimulus distance of 57 cm with a semiautomatic procedure. 95 Although optimal optical cor- …”
Section: A Caveat-effect Of Retinal Image Quality On Pergmentioning
confidence: 99%
“…The effects are readily understood when the low-pass nature of defocus [92][93][94] and the PERGs linear contrast-amplitude characteristic are taken into account. 49,51 To avoid false positive results, we perform PERG-glaucoma testing only on eyes with a visual acuity Ն0.8, tested at the PERG-stimulus distance of 57 cm with a semiautomatic procedure. 95 Although optimal optical cor- …”
Section: A Caveat-effect Of Retinal Image Quality On Pergmentioning
confidence: 99%
“…1316 As the PERG amplitude in response to reversing gratings depends on the spatio-temporal parameters of the visual stimulus, 6, 1719 it can be maximized by choosing the appropriate conditions (maximum contrast, 1–2 cycles/degree spatial frequency, ~ 8 Hz temporal frequency). 17, 18 It has been previously shown that stimulus conditions that maximize PERG response also elicit maximal, sustained increase of blood flow (~ 40% compared to baseline) at the neuro-retinal rim of the optic disk, 5, 20, 21 which remains stable over ~ 1 hour of measurements.…”
Section: Methodsmentioning
confidence: 99%
“…(Hess & Baker, 1984; Porciatti et al , 1992) The PERG amplitude increases progressively with increasing contrast. (Zapf & Bach, 1999; Porciatti et al , 2005) The PERG amplitude also increases using gratings with square-wave in space and time compared to sine-wave. Therefore, choosing a pattern with square-wave in space and time, with highest contrast, and with peak spatial and temporal frequency allows maximizing response amplitude.…”
Section: Methodsmentioning
confidence: 99%